Multiple cavitary pulmonary nodules in association with pyoderma gangrenosum: case report Múltiplos nódulos pulmonares cavitados em associação com pioderma gangrenoso: relato de caso - Maraya de Jesus Semblano Bittencourt; Luciana Fontenele Brito Soares; Lilia Sampaio Lobato; Alexandre Dias Mançano; Helandro Stuart Castro Leandro; Diana Mendes da Fonseca (Sociedade Brasileira de Dermatologia, 2012)
Pyoderma gangrenosum is a rare neutrophilic disease of unknown origin that is associated with systemic diseases in 50% of cases. It is characterized by erythematous-violaceous nodular lesions that quickly progress to painful ulcers, with undermined edges, necrotic-hemorrhagic, varying in size and depth, located mainly in the lower limbs. Extracutaneous locations of pyoderma gangrenosum are rare, usually involving the lungs; the main differential diagnosis in these cases is Wegener granulomatosis. We report a case of pyoderma gangrenosum, which showed multiple cavitary lung nodules, with good response to high doses of steroids. Once excluded the possibility of Wegener granulomatosis, the authors concluded that it was the manifestation of systemic pyoderma gangrenosum with pulmonary involvement. Pioderma gangrenoso é doença neutrofílica rara de etiologia desconhecida, que se associa a doenças sistêmicas em 50% dos casos. Caracteriza-se clinicamente por lesão nodular eritematoviolácea ou pústula que progride rapidamente para úlcera dolorosa, de bordas irregulares, fundo necrohemorrágico e localização preferencial nos membros inferiores. Manifestações sistêmicas do Pioderma gangrenoso são raras, envolvem geralmente os pulmões e o principal diagnóstico diferencial nestes casos é a granulomatose de Wegener. Relatamos um caso de paciente portador de pioderma gangrenoso que apresentava múltiplos nódulos pulmonares cavitados, com boa resposta a altas doses de corticoterapia. Uma vez excluída a possibilidade de granulomatose de Wegener, os autores concluíram tratar-se da manifestação sistêmica do pioderma gangrenoso.